Identification of four novel associations for B-cell acute lymphoblastic leukaemia risk - Vijayakrishnan, Jayaram; Qian, Maoxiang; Studd, James B.; Yang, Wenjian; Kinnersley, Ben; Law, Philip J.; Broderick, Peter; Raetz, Elizabeth A.; Allan, James; Pui, Ching-Hon; Vora, Ajay; Evans, William E.; et al. (Nature communications, 2019)
There is increasing evidence for a strong inherited genetic basis of susceptibility to acute lymphoblastic leukaemia (ALL) in children. To identify new risk variants for B-cell ALL (B-ALL) we conducted a meta-analysis with four GWAS (genome-wide association studies), totalling 5321 cases and 16,666 controls of European descent. We herein describe novel risk loci for B-ALL at 9q21.31 (rs76925697, P = 2.11 × 10 −8 ), for high-hyperdiploid ALL at 5q31.1 (rs886285, P = 1.56 × 10 −8 ) and 6p21.31 (rs210143 in BAK1 , P